OUTCOME OF SURGICAL HAEMORRHOIDECTOMY BY OPEN AND CLOSED TECHNIQUES: Outcome of Surgical Haemorrhoidectomy - Rathore, Maj Muhammad Omar; Shukr, Irfan (Pakistan Armed Forces Medical Journal, 2010)
Objectives: To compare the outcome of surgical haemorrhoidectomy by open and closed techniques in terms of “Post operative pain” and “Early stricture formation”. Study Design: Randomized Controlled Trial (RCT). Place and Duration of Study: Department of Surgery, Combined Military Hospital Rawalpindi from January 2007 to November 2007. Patients and Methods: A total of 100 patients were included in the study which was categorized into two equal study groups. Group A underwent open haemorrhoidectomy and Group B underwent closed haemorrhoidectomy under spinal anaesthesia. Postoperative pain was ascertained at 6, 12 and 24 hours after operation by visual analogue scale. Early stricture formation was assessed by per rectal examination three weeks after haemorrhoidectomy. Results: The mean post operative pain severity score according to linear analogue scale was 4.20 (SD = 0.782) and 4.94 (SD = 1.420) after six hours, 3.26 (SD = 0.803) and 3.90 (SD = 1.147) after twelve hours and 2.20 (SD = 0.782) and 2.98 (SD = 0.937) after twenty four hours in Group A and B respectively. At all the three time intervals, the differences in means of post operative pain severity were statistically significant with P-value < 0.05. The frequency of early stricture formation in group A was 6 % while in group B was 4 % and this difference was statistically insignificant (P-value = 0.646). Conclusion: The study concludes that the post operative pain in cases of open haemorrhoidectomy is less than that in closed procedure and there is no significant difference in stricture formation between the two procedures.